The New Face of People Power: An Exploratory Study on the Potential of Social Media for Combating Corruption in Indonesia - Hendi Yogi Prabowo; Rizki Hamdani; Zuraidah Mohd Sanusi (Australasian Accounting, Business and Finance Journal, 2018)
This paper is based on the authors’ study to assess the current state of anti-corruption movement in Indonesia. The main purpose of this study is to explore the potential of social media to be used as an effective tool in combating corruption in public sector. To achieve its objectives this study applies multiple behavioral perspectives in assessing the corruption problem in the Indonesian public sector. This study is of qualitative exploratory nature in which the authors utilized a mixed methods approach comprising of a systematic literature review, archival and data analysis, and case studies on corruption in the Indonesian public sector to assess the potential of social media to be used as an anti-corruption measure. This study also uses the Social Network Analysis (SNA) to illustrate the potential of social media as a means for citizens to participate in an anti-corruption movement in Indonesia. Overall, this study demonstrates that the growth and development of Information and Communication Technologies (ICTs) in Indonesia has had a profound effect on how people interact with each other by, among other things, using social media platforms. Such interaction includes discussions and dissemination of news and information related to corruption. As the conventional punishment oriented approaches have not had a lot of success in mitigating the corruption problem in Indonesia, engaging citizens to actively participate in the anti-corruption movement may increase the chance of success in eradicating corruption in the future.
Keywords: corruption; Indonesia; fraud triangle; ICTs; social media; behavior.